Management of Endurance Athletes with Flow Limitation in the Iliac Arteries: A Case Series. (2018) - Khan, Assad; Al-Dawoud, Marwan; Salaman, Robert; Al-Khaffaf, Haytham
Abstract : Introduction: Vascular surgeons increasingly encounter flow limitation of iliac arteries (FLIA) in endurance athletes. An experience of managing this condition is reported. Report: This is a retrospective cohort analysis of prospectively collected data at a single vascular centre. Between 2001 and 2017, 12 athletes with exercise induced pain underwent investigation and assessment. Patients with significant radiological findings (iliac kinking ± stenosis demonstrated on duplex ultrasound or catheter angiography) and dynamic flow changes (marked reduction in ankle brachial pressure indices following exertion, or increase in the common iliac artery peak systolic velocity during hip flexion on duplex) underwent surgery after trialling conservative management; the majority were open iliac shortening procedures. Patients with radiological findings, but no dynamic flow changes were managed conservatively. All patients were followed up. Discussion: There were 10 men and two women with a median age of 40 years. Nine patients had iliac kinking (five in isolation, four associated with stenosis), two had stenosis, and one had no iliac disease. Eight patients had severe symptoms (absolute loss of power on maximal exertion) demonstrated dynamic post-exertional flow changes. Seven patients successfully underwent surgery, returning to their sport at similar intensity. One procedure was abandoned owing to severe adhesions from a prior procedure. This patient subsequently changed sport. Three patients with mild symptoms (two had reduction in power at maximal intensity, one was an incidental finding) and who demonstrated no clinical signs of FLIA continued their sport at a lower intensity. Kinking of the iliac arteries in athletes can occur with or without of iliac stenosis. Patients with the most severe iliac symptoms demonstrate dynamic post-exertional flow limitation and may benefit from surgery following a period of conservative management. Patients who have milder symptoms and no dynamic exercise flow limitations can be managed conservatively. Highlights: This series looks at iliac kinking as a cause of flow limitation in iliac arteries (FLIA) of athletes. Iliac kinking is often overlooked in favour of endofibrosis. The data demonstrate that iliac kinking can result in FLIA. Some of these patients would benefit from surgery, after trailing conservative management.